The Role of Mycorrhizal Fungi in Forest Ecosystem Health - Nasser, Maha Al; Mansour, Youssef Al; Sayid, Nisreen Al (Journal of Selvicoltura Asean, 2024)
Mycorrhizal fungi play a crucial role in forest ecosystems, facilitating nutrient uptake and enhancing plant health. These symbiotic relationships are vital for the resilience and productivity of forests, yet their contributions to ecosystem health remain underexplored. This study aims to investigate the specific roles of mycorrhizal fungi in promoting forest ecosystem health by assessing their impact on nutrient cycling, soil structure, and plant diversity. A combination of field surveys and laboratory analyses was employed, focusing on various forest types with differing mycorrhizal associations. Data were collected on soil properties, fungal biodiversity, and plant growth metrics. The results indicate that forests with diverse mycorrhizal communities exhibit improved soil health, characterized by higher nutrient levels and better moisture retention. Additionally, these forests support greater plant diversity and demonstrate enhanced resilience to environmental stressors. The findings underscore the importance of mycorrhizal fungi in maintaining forest ecosystem health and highlight the need for conservation strategies that protect these critical organisms. In conclusion, mycorrhizal fungi are essential for nutrient cycling and overall forest vitality, suggesting that their preservation should be a key component of forest management practices.